PENDAMPINGAN SANTRI DENGAN PELATIHAN PEMBUATAN JAJANAN PANGAN DAN MINUMAN UNTUK MENAMBAH PENGHASILAN KANTIN PONDOK PESANTREN PUTRI UTARA - Biati, Lilit; Suprapto, Ribut; Mamlukhah, Mamlukhah (Proceedings of Annual Conference on Community Engagement, 2023)
Before the establishment of this canteen, there were several stalls inside the Putri Utara Islamic Boarding School, which were sold directly by women in the neighborhood around the Darussalam Blokagung Islamic Boarding School. Due to the lockdown, the women were no longer able to sell and at that time the shop was completely closed, so the Board of Trustees and Management of the North Putri Islamic Boarding School took a policy by opening a canteen and providing storage for the sale of snacks and drinks. The canteen is one of the sources of financial income from various financial income obtained by the North Putri Islamic boarding school. However, the income obtained by the canteen is still minimal. By conducting training in making beverage products, it is hoped that they will be able to produce their own beverages for resale. In this service, a strategy approach is used with the principles of community development based on Asset Based Community Driven Development (ABCD). To improve the quality of marketing products, a training activity was held to make snack products in the form of food and drinks.